Hello, Crabby! (Acorn, ,, 2019)
Crabby is not a happy crab, in fact Crabby is quite crabby, so pushy Plankton, who is always trying to cheer up fellow marine creatures, bakes Crabby a cake--but will Crabby finally smile?

A unicorn, a dinosaur, and a shark were riding a bicycle (Penguin Workshop, 2024)
"According to the narrator of this book, a unicorn, a dinosaur, and a shark were riding a bicycle. But they say that's not true, and they just want to take a load off for once. They're tired of being told what to do by the bossy storyteller! And who is a reader supposed to believe, anyway--a book's narrator or its characters?"--Book jacket.